2017
DOI: 10.1111/opec.12102
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship between crude oil price, energy consumption and carbon dioxide (CO2) emissions in Ecuador

Abstract: This study examines the causal relationship between crude oil price, energy consumption and CO2 emissions in Ecuador over the period 1971–2013 incorporating indicators of economic performance. ARDL bounds testing approach to cointegration provides evidence of cointegration between the variables in the presence of structural break in the series. The long‐run effect of energy consumption on CO2 emissions in the oil‐dependent economy is found to be positive and statistically significant. The long‐run and short‐ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 37 publications
(49 reference statements)
4
19
0
1
Order By: Relevance
“…According to Di Bella et al (2015), the subsidization of energy consumption in the oil-dependent Latin American economies boosted by income from oil resource exports promoted the growth and development of energy-intensive sectors such as car manufacturing industry thereby increasing energy-intensive consumption. Similar economic conditions have been documented for other heavily dependent net oil-exporting economies, including Algeria (see Fuinhas and Marques 2013), Saudi Arabia (see Alshehry and Belloumi 2015) and Ecuador (see Nwani 2017). Regardless of good intentions, the results of this study show that the economic conditions created by fossil fuel subsidies and low fuel prices in Venezuela may have generated increased consumption of fossil fuels, thereby intensifying their negative effects on the environment by increasing CO 2 emissions.…”
Section: Discussion and Policy Implicationssupporting
confidence: 79%
See 1 more Smart Citation
“…According to Di Bella et al (2015), the subsidization of energy consumption in the oil-dependent Latin American economies boosted by income from oil resource exports promoted the growth and development of energy-intensive sectors such as car manufacturing industry thereby increasing energy-intensive consumption. Similar economic conditions have been documented for other heavily dependent net oil-exporting economies, including Algeria (see Fuinhas and Marques 2013), Saudi Arabia (see Alshehry and Belloumi 2015) and Ecuador (see Nwani 2017). Regardless of good intentions, the results of this study show that the economic conditions created by fossil fuel subsidies and low fuel prices in Venezuela may have generated increased consumption of fossil fuels, thereby intensifying their negative effects on the environment by increasing CO 2 emissions.…”
Section: Discussion and Policy Implicationssupporting
confidence: 79%
“…It also allows for simultaneous testing of the long-run and short-run relationships between variables in small and large sample sizes and provides unbiased coefficients of variables along with valid t-statistics even when the explanatory variables are endogenous (Pesaran et al 2001). These statistical features have made ARDL bounds approach to cointegration popular among researchers in recent years (see Shahbaz et al 2013; (3) Crude Oil Price (US$ per barrel) General government final consumption expenditure Time series plot of the study variables (Data source: see Table 2) et al , 2017Mahalik et al 2017;Rafindadi 2016;Khraief et al 2018 among others). The implementation of ARDL bounds approach involves testing for the presence of a longrun relationship based on the log-linear specification in the four equations using a dynamic unrestricted error correction model (UECM) framework that integrates the short-run dynamics with the long-run equilibrium without losing any long-run information.…”
Section: Empirical Model and Estimation Methodsmentioning
confidence: 99%
“…Zambrano-Monserrate et al (2016), using an autoregressive distributed lag bounds testing approach, find evidence of a long-run environmental Kuznets curve (EKC) for Ecuador from 1971 to 2011 for economic growth and for energy on carbon dioxide emissions (CO 2 ). Nwani (2017), instead, finds a unidirectional causality that flows from CO 2 emissions to economic growth and confirms the positive and statistically significant long-run effect of energy consumption on CO 2 emissions. Robalino-López et al (2014a), using a variation of the Kaya identity, find that it is possible to control the CO 2 emissions if GDP growth is combined with an increase in the use of renewable energy.…”
Section: Introductionmentioning
confidence: 62%
“…It is, nevertheless, shocking that very limited number of the present researches have measured the connecting the impact of price of crude oil on the consumption of energy and CO2 emissions in oil endowed and abundant nations, where receipt from crude oil export is a serious means of fiscal spending that creates a lots of economic events. Using Ecuador as a case study, Nwani (2017) studied the connecting relationship among price of crude oil, CO2 emissions and energy consumption for period spanning 1971 to 2013 and include economic growth by means of income per capita. The study was possible with the help of ARDL and granger causality test and the outcome showed that high oil revenue generate economic situations that require additional consumption of energy which significantly resulted in CO2 emissions in the economy for the two periods.…”
Section: Literature Reviewmentioning
confidence: 99%